Antiviral mono- and bis-prenylated C6–C3 derivatives from the roots of Illicium oligandrum. Issue 22 (2nd June 2016) - Ma, Shuang-Gang; Gao, Ya; Wang, Hui-Qiang; Li, Li; Liu, Yun-Bao; Qu, Jing; Li, Yong; Xu, Song; Lv, Hai-Ning; Li, Yu-Huan; Yu, Shi-Shan
Abstract: Four new bis-prenylated C6 –C3 derivatives, illioliganpyranones B–C (1 and4 ) and illioliganfuranones E–F (3 and5 ), and six new mono-prenylated C6 –C3 compounds, illioliganfuranone G (2 ), illioliganfuranol A (6 ), illioliganpyranone D (7 ), illioliganones J–K (8 and9 ), and illioliganpyranol A (10 ), were isolated from the CHCl3 extract of Illicium oligandrum roots. The structures of1 –10 were determined through interpretation of their spectroscopic data, including 1D and 2D NMR, HRESIMS, and CD experimental results, and the modified Mosher's method. The structure of illioliganpyranone B (1 ) was confirmed by single-crystal X-ray diffraction analysis. Compounds1 and3 –5 are the first examples of linear bis-prenylated C6 –C3 derivatives featuring ether bond connectivity. The in vitro activity of these compounds was evaluated against Coxsackievirus B3 (CVB3) and influenza virus A/Hanfang/359/95 (H3N2). Compounds1, 3 –5 and6 demonstrated potent antiviral activity against CVB3, with IC50 values ranging from 3.70 to 11.11 μM and SI values ranging from 5.2 to 21.1, whereas compounds6 and7 were found to exhibit potent activity against influenza virus A H3N2 with IC50 values of 5.55 and 2.24 μM and SI values of 18.0 and 8.6, respectively. Graphical abstract: